To what extent is bruxism associated with musculoskeletal signs and symptoms? A systematic review. (31st May 2019) - Baad‐Hansen, Lene; Thymi, Magdalini; Lobbezoo, Frank; Svensson, Peter
Abstract: The aim of the present systematic review was to answer the overall research question: "To what extent is bruxism associated with musculoskeletal signs and symptoms?". The review was performed in accordance with the PRISMA guidelines. A PubMed search of articles published until 23 November 2017 was conducted. The search string included both MeSH terms and text words. Results were presented in categories according to study design, study population (eg, adults, children), bruxism sub‐type (awake, sleep), assessment methods for bruxism and musculoskeletal symptoms (self‐report, validated test) and type of outcome (pain, non‐painful musculoskeletal symptoms). It could be concluded that bruxism is to some extent associated with musculoskeletal symptoms, even though the evidence is conflicting and seems to be dependent on many factors, such as age, whether the bruxism occurs during sleep or wakefulness, and also the quality of the diagnostic methodology regarding bruxism and musculoskeletal signs and symptoms. The literature does not support a direct linear causal relationship between bruxism and such symptoms, but points more in the direction of a multifaceted relationship dependent on the presence of other risk factors. Pain is by far the most commonly assessed symptom, whereas non‐painful musculoskeletal symptoms have generally not been systematically evaluated. In the light of recent findings indicating that non‐painful symptoms may precede TMD pain, it is suggested to increase the scientific focus on non‐painful musculoskeletal symptoms in future studies. Also, future studies should use validated methods for case definition and outcome assessments.